United Kingdom : 2002 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the United Kingdom. (IMF Staff Country Reports; Country Report, 2003)
This 2002 Article IV Consultation highlights that the real GDP of the United Kingdom increased at an average rate of some 2.8 percent, and the unemployment rate halved to below 5 percent by April 2001. Inflation, which has been low since the mid-1990s, was-on a harmonized basis-about 1.5 percent, below the European Union average. Real output growth decelerated in 2002, but remained above that of other large European countries. Notwithstanding the global slowdown, the United Kingdom economy grew by 1.7 percent owing mainly to buoyant private consumption as well as increased public spending.